KONSEP BERFIKIR DALAM PEMACAHAN MASALAH MAHASISWA PROGRAM STUDI BIMBINGAN DAN KONSELING UNIVERSITAS PROF. DR. HAZAIRIN, SH. BENGKULU - Juwanto -; Zumkasri - (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2017)
This study aims to determine: (1) the concept of thinking in problem solving Study Program Student Guidance and Counseling (2) What factors influence decision the decision to solve the problem. The method used in this research is qualitative descriptive. The study revealed about events and other symptoms of what is or what is actually happening. Subjects in this study were students Prodi guidance and counseling force in 2016. The data collection techniques in this study were collected by using interview, observation and documentation. Data analysis technique is done with the concept of data reduction, data display and conclusion. Results of the research findings are (1) the concept of thinking in problem solving Study Program Student Guidance and Counseling, has some concept of a) was based on the character, the criteria, the argument, consideration thoughts, viewpoints and weight problems. b) Some of the students have no concept of critical thinking skills, the skills to use reasoning to assess the reasonableness of an idea and reasonable consideration. c) The weakness of berfkiri creative prowess, that prowess in creating ideas, find an alternative, and the courage to try). (2) Factors influencing decision making in solving problems that have two a) internal factors, these factors appear in a student, in individual problem-solving process plays an important role in making a decision. By berfkir critically, capable memenej and emotional self-control and students are able to take decisions that terentaskan problem. This factor arises because the experience of logic, take risks, social transmission, self-control and pendewaasaan, b) External factors, these factors emerge from outside of the student, in the process of solving the issue and decision making of students affected by some aspects such as family environment, community , the environment and the environment in which work / round. Keywords: Thinking, Problem Solving, Guidance and Counseling